Leasing: An Alternative Financing Mechanism for SMEs - Hossain, Md. Mosharref (ABC Journal of Advanced Research, 2013)
In almost every developing country Small and Medium enterprises (SMEs) are treated as the engine for economic growth and the availability of external finance for them is a topic of significant research interest to academics and policy makers around the globe. SMEs need improved access to finance especially for acquiring capital equipment and applications of new technology for operations. However, their access to finance is restricted because they do not have reliable credit histories, adequate capitalization or additional assets for collateral. Most of the financial institutions are reluctant to provide term loans or cash flow based lending to the SME sector. Thus, SMEs face severe disadvantages while trying to obtain financing relative to larger and more established firms. On the other hand, leasing is an asset-backed, term financing product. It focuses basically on the ability of lessee’s cash flow generation from their regular business operations to service the lease payment, rather than on the asset base. In this connection, this paper investigates how as an alternative financing mechanism, leasing can be the useful tool in facilitating greater access to finance for SMEs. From the survey of the paper it is found that out of 46.67% who got the access into the formal financial institutions only 7.14 per cent of the enterprises avail the lease facilities. So it is strongly suggested that developing the leasing sector as a means of delivering finance increases the range of financial products in the marketplace and provides a route for accessing finance to SMEs that would otherwise be impossible.